Congenital isolated Iso–Kikuchi syndrome in a newborn. Issue 10 (7th September 2015) - Valerio, Enrico; Favot, Francesca; Mattei, Ilaria; Cutrone, Mario
Key Clinical Message Classic CO (also called Iso–Kikuchi syndrome) represents a benign, isolated condition associated with normal patient outcome. Nevertheless, clinical follow‐up and/or further clinically‐based tests are needed to exclude other nail diseases associated with multisystem pathology; complete family history is also important to determine sporadic or hereditary transmission of such condition.